Dimerization of the BASIC PENTACYSTEINE Domain in Plant GAGA-Factors is Mediated by Disulfide Bonds and Required for DNA-Binding. - L. Theune, Marius; Hummel, Sabine; Jaspert, Nina; Lafos, Marcel; Wanke, Dierk (Journal of Advances in Plant Biology, 2017)
GAGA-binding proteins in plants are encoded by the BARLEY B-RECOMBINANT / BASIC PENTACYSTEINE (BBR/BPC) family, which can be spilt into several groups on the basis of sequence divergence. The proteins of the different groups share an evolutionary conserved BASIC PENTACYSTEINE (BPC) domain at their very C-terminus that is important for DNA binding. Hallmark of this domain are five Cysteines at defined positions and spacing, which are considered to form a zinc-finger like structure that is involved in GAGA-motif recognition. Here, we report the formation of stabile homodimers between Arabidopsis thaliana group I member BPC1 or between group II member BPC6 in SDS-PAGE. Serial mutations of the highly conserved five Cysteines in the BPC domain of Arabidopsis thaliana BPC1 were tested for their capacity to bind to GAGA-motifs by DPI-ELISA. Our results do not support the idea of a direct involvement of these residues in making physical contact with the DNA, e.g. by formation of a zinc-finger structure. Instead, the data implies an indispensable function for the five Cysteines in homodimerization and stabilization of the protein structure by disulfide bonds. Accordingly, protein folding and structure prediction suggests the formation of a scaffold for dimerization that is supported by three intermolecular and one intramolecular S-S bond. The high degree of conservation between the BPC domains from the different groups and from different species denotes that this role for the five Cysteines might be evolutionary retained.
Keywords: BBR/BPC-family; DNA-binding; inter- and intra-molecular disulfide bonds; protein-protein interaction; DPI-ELISA; I-TASSER; protein structure prediction; putative zinc-finger domain